FINANCING OF LOCAL BUDGETS ON THE EXAMPLE OF IVANO-FRANKIVSK REGION - Kokhan, I.V. (The actual problems of regional economy development, 2019)
The dominant tendencies of the current stage of development of the national economy are the strengthening of processes of regionalization, which involve shifting attention in decision-making on socio-economic development to the regional level, with a simultaneous shift of emphasis to the discovery of internal potential. On the other hand, new challenges caused by global and international imbalances, which negatively affect the socio-economic development of Ukrainian regions, are a barrier that prevents local governments from pursuing an independent development policy. In this context, the reform processes of public finances currently experienced by Ukraine are relevant and require rethinking the patterns of influence of financial policy instruments and levers on the socio-economic development of the regions. The socio-economic development of the region is characterized by uneven and contradictory results and requires the intensification of structural adjustment and the search for an approach to structural transformation. The formation of an effective economic structure is an important issue that needs priority in the context of the strategic objectives of the country's macroeconomic development. In developed countries, the mechanism of state regulatory influence plays a key role in ensuring sustainable economic growth. Investigating the structure of the economy of the region, it is necessary to pay attention to structural changes, without which a complete study of the transformation system is impossible. Structural policy is a general strategy for maximizing socio-economic development through the implementation of priority government programs and projects. Against the background of decentralization processes in Ukraine, the role of budget policy, which determines the scope of primary GDP distribution, becomes an active element of the system of state regulation and a decisive factor in the management of economic and social processes and their development. This stipulates the need for scientific research aimed at improving the processes of budget financing of socio-economic development of Ukrainian regions. The article deals with the nature and structure of financial support of local governments. The analysis of revenues and expenditures of local budgets of the Ivano-Frankivsk region is carried out. The priority of regional financial policy is to ensure the socio-economic development of the region. The development of local self-government with self-sufficient local budgets and the transfer of certain powers to local authorities determine the formation of the budget process in accordance with European standards, which requires the search for new reserves of financial support for the region, in accordance with its resource and human resources.